2000
DOI: 10.1046/j.1365-3180.2000.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal light environment on germination and morphological characteristics of Sicyos deppei seeds

Abstract: The effect was studied of sunlight and far‐red (FR) light during seed development, on seed quality and germination of Sicyos deppei G. Don. Seeds exposed to FR during development were lighter in colour and their weight, size and water content were significantly lower. Less than 10% of non‐scarified freshly harvested seeds germinated. Scarified, freshly harvested seeds developed under sunlight had a partially negative photoblastic response; both red (R) and FR light inhibited germination. The highest and fastes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Similarly, freshly harvested seeds of the weedy Sicyos deppei developed under sunlight had a partially negative photoblastic response; both red and far-red light inhibited germination. After 6 months of storage, the seed permeability increased and the partially negative photoblastic response was lost (Orozco-Segovia et al, 2000). The need for high temperature and light to achieve greater germination in fresh seeds of P. juliflora was significantly reduced after seed storage.…”
Section: Article In Pressmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, freshly harvested seeds of the weedy Sicyos deppei developed under sunlight had a partially negative photoblastic response; both red and far-red light inhibited germination. After 6 months of storage, the seed permeability increased and the partially negative photoblastic response was lost (Orozco-Segovia et al, 2000). The need for high temperature and light to achieve greater germination in fresh seeds of P. juliflora was significantly reduced after seed storage.…”
Section: Article In Pressmentioning
confidence: 98%
“…It has been reported that fresh seeds usually germinate under specific narrow range of conditions, but such conditions gradually become wider as a result of seed storage (Gutterman et al, 1998;Orozco-Segovia et al, 2000;Qaderi et al, 2003). In the desert herb Plantago coronopus, seeds stored for 2 months germinated under a narrow range of lower temperatures (5-15 1C), but germinated under a wider range of high temperatures (15-30 1C) when stored in their inflorescences under natural desert habitat conditions for 1 year (Gutterman et al, 1998).…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the germination characteristics of a seed are determined during the course of its development, and the environmental conditions experienced by parent plants during seed production and maturation can strongly influence the degree and type of dormancy in the seed (Fenner, 1985: 79; Kegode & Pearce, 1998; van Hinsberg, 1998; Orozco‐Segovia et al ., 2000). In the case of L. maritima , the environmental inhibition of germination might have been under selection, as responses of seeds to various environmental factors have a genetic basis (Baskin & Baskin, 1998: 186; Foley & Fennimore, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Many wavebands within the light spectrum are of biological significance, including photosynthetically active radiation (PAR) (400-700 nm) for photosynthesis and UVA/UVB (350-500) for stomatal opening and induction of phototropism (Smith 1982;Grant 1997;Hart 1998). The ratio of red (660) to far-red (730) light (R:FR) is important for the detection of competition Ballaré et al 1990) and regulation of seed dormancy and germination (Lee et al 1996;Orozco-Segovia et al 2000), stem elongation and leaf area expansion (Morgan 1981), apical dominance , and internode expansion (Morgan and Smith 1978a;Ballaré et al 1990;Grant 1997). Generally, plants respond to a decrease in R:FR by increasing leaf area and internode length in an effort to access more available light (Morgan and Smith 1978b;Smith 1981Smith , 1982.…”
Section: Introductionmentioning
confidence: 99%